2022
DOI: 10.1007/s10311-022-01509-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and potential applications of cyclodextrin-based metal–organic frameworks: a review

Abstract: Metal–organic frameworks are porous polymeric materials formed by linking metal ions with organic bridging ligands. Metal–organic frameworks are used as sensors, catalysts for organic transformations, biomass conversion, photovoltaics, electrochemical applications, gas storage and separation, and photocatalysis. Nonetheless, many actual metal–organic frameworks present limitations such as toxicity of preparation reagents and components, which make frameworks unusable for food and pharmaceutical applications. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 145 publications
0
7
0
Order By: Relevance
“…21 Therefore, considering the advantages of g-CD-MOFs, such as being non-toxic, edible, renewable, biodegradable, and high specific surface area, among others, they can be a novel class of porous extension frameworks. 18 Studies have indicated that g-CD-MOFs are excellent carriers for bioactive substances, 20,22,23 including curcumin, 19 menthol, 24 glycyrrhizin acid, 25 vitamin A palmitate, 26 catechin 27 and as a drug carrier. 28 However, although various methods have been used to encapsulate OEO, no studies have been reported about OEO encapsulated in g-CD-MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…21 Therefore, considering the advantages of g-CD-MOFs, such as being non-toxic, edible, renewable, biodegradable, and high specific surface area, among others, they can be a novel class of porous extension frameworks. 18 Studies have indicated that g-CD-MOFs are excellent carriers for bioactive substances, 20,22,23 including curcumin, 19 menthol, 24 glycyrrhizin acid, 25 vitamin A palmitate, 26 catechin 27 and as a drug carrier. 28 However, although various methods have been used to encapsulate OEO, no studies have been reported about OEO encapsulated in g-CD-MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs are a class of multifunctional composite porous crystalline materials in which organic ligands and inorganic metal centers are connected by self-assembly, which can be used as gas storage and separation, catalysts for organic transformations, biomedicine, sensors, photovoltaics and energy conversion. [246][247][248] However, conventional MOFs are synthesized by time-consuming hydrothermal or solvothermal methods, which generally require hours or days for the crystallization and formation of porous networks. Droplet-based microfluidic devices have a high surface-tovolume ratio, efficient mixing and heat transfer efficiency and can eliminate channel blockage and significantly increase the reaction rate; thus, they are widely used in high-throughput biological and biochemical screening experiments.…”
Section: Synthesis Of Composite Micro/nanomaterialsmentioning
confidence: 99%
“…[40,84,89] Cyclodextrins (CDs) are considered the most significant organic ligands among various saccharides due to their intrinsic hydrophobic inner cavity, hydrophilic outer surface, and molecular recognition properties. [90][91][92][93][94][95][96][97][98][99][100][101] The first case of cyclodextrin-based MOF was reported in 2010 by Wang et al [102] , who used K + or Rb + ions were coordinated with six γ-CD units to synthesize a porous γ-CD based MOFs. The incorporation of chitosan's intrinsic hydrophobic inner cavity properties into MOFs in this study has successfully enhanced the potential applications of MOFs in drug loading, controlled drug release, and sewage purification.…”
Section: Saccharides As Organic Ligandsmentioning
confidence: 99%
“…Therefore, they also can serve as organic ligands for the synthesis of MOFs [40,84,89] . Cyclodextrins (CDs) are considered the most significant organic ligands among various saccharides due to their intrinsic hydrophobic inner cavity, hydrophilic outer surface, and molecular recognition properties [90–101] …”
Section: The Synthesis and Surface Functionalization Of Mofsmentioning
confidence: 99%